Morphological, Physiological, Biochemical, and Molecular Characterization of Fungal Species Associated with Papaya Rot in Cameroon - Moussango Victor Davy; Voundi Olugu Steve; Tchabong Raymond Sammuel; Marie Ampères Bedine Boat; Ntah Ayong Moise; Anna Cazanevscaia Busuioc; Priscile Ebong Mbondi; Andreea Veronica Dediu Botezatu; Manz Koule Jules; Maria Daniela Ionica Mihaila; Rodica Mihaela Dinica; Sameza Modeste Lambert (Journal of Fungi)
Post-harvest decay of Carica papaya L. is the primary cause of deterioration in papaya quality and the low economic impact of this sector in Cameroon. Field surveys conducted by teams from the Ministry of Agriculture and Rural Development (MINADER) in Cameroon have primarily associated these decays with fungal attacks. However, to date, no methodological analysis has been conducted on the identification of these fungal agents. To reduce post-harvest losses, rapid detection of diseases is crucial for the application of effective management strategies. This study sought to identify the fungal agents associated with post-harvest decay of papaya cv Sunrise solo in Cameroon and to determine their physiological and biochemical growth characteristics. Isolation and pathogenicity tests were performed according to Koch’s postulate. Molecular identification of isolates was achieved by amplification and sequencing of the ITS1 and ITS4 regions. Phylogenetic analysis was based on the substitution models corresponding to each fungal genus determined by jModeltest, according to the Akaike information criterion (AIC). Fungal explants of each identified species were subjected to variations in temperature, pH, water activity, and NaCl concentration. The ability to secrete hydrolytic enzymes was determined on specific media such as skimmed milk agar for protease, peptone agar for lipase, and carboxymethylcellulose for cellulase. These experiments allowed the identification of three fungi responsible for papaya fruit decay, namely Colletotrichum gloeosporioides, Fusarium equiseti, and Lasiodiplodia theobromae. All three pathogens had maximum mycelial growth at a temperature of 25 ± 2 °C, pH 6.5, NaCl concentration of 100 µM, and water activity (aw) equal to 0.98. The three fungal agents demonstrated a strong potential for secreting cellulases, lipases, and proteases, which they use as lytic enzymes to degrade papaya tissues. The relative enzymatic activity varied depending on the fungal pathogen as well as the type of enzyme secreted. This study is the first report of F. equiseti as a causal agent of papaya fruit decay in Cameroon.